Effect of Cutting Parameter Toward The Surface Roughness Applied In Turning Tool Steel Material - Gatot Setyono; Slamet Riyadi; Muharom; Ong Andre Wahyu Riyanto; Sigit Pratama (P3M Politeknik Negeri Cilacap, 2022)
In this study, the effect of the tool-tip radius and cutting process parameters on the quality of the machining process experimentally on the use of SKD 11 tool steel material. Several radius (0.80 mm, 1.20 mm, 1.60 mm) and the parameters of the cutting process, specifically feed rate, cutting speed, and depth of cut. The ANOVA method used in this study aims to analyze the cutting process parameters on the surface quality of the workpiece and the cutting force. The analysis of this research results in certain conditions in which the feed rate significantly affects surface quality. However, this is contrary to the depth of cut parameter, which affects the cutting force. This study also observed the effect of the tooltip radius on the optimal surface quality when using a 0.80 mm radius. The second-order regression modeling used in this analysis shows a very good level of accuracy, with the correlation value of accuracy ranging from 96% to 98%.